fNIRS as a biomarker for X-linked neurodevelopmental disorders: leveraging visual processing to assess brain function? - Scaffei, Elena; Bosetti, Chiara; Battini, Roberta; Fagiolini, Michela; Baroncelli, Laura (Frontiers in Neuroscience, 2025)
Neurodevelopmental disorders (NDDs) cause profound intellectual and physical impairment, yet therapeutic progress remains hindered by the lack of quantitative, unbiased, and non-invasive biomarkers to monitor disease onset and progression. Visual evoked potentials (VEPs) have emerged as promising functional biomarkers for X-linked NDDs, with reduced VEP amplitudes correlating with disease severity. Complementary approaches, like functional Near Infrared Spectroscopy (fNIRS), offer a non-invasive additional tool to assess brain metabolism, monitor disease progression, and evaluate therapeutic responses. This perspective explores the potential of fNIRS in studying visually evoked hemodynamic responses (vHDR) across different age groups, demonstrating its reliability in capturing task-specific cortical activation and tracking brain maturation even in challenging populations. Notably, fNIRS identifies unique vHDR patterns in conditions like optic neuritis, myopia, glaucoma, and migraines, validating its role as a biomarker for disease severity and treatment efficacy. Moreover, fNIRS has proven effective in detecting early neural deficits in high-risk infants, including pre-term newborns. Preclinical studies support that visually induced hemodynamic changes can differentiate healthy from pathological conditions in X-linked NDDs. However, direct evidence from human cohorts with X-linked NDDs remains limited, highlighting the urgent need for further research to validate the potential of visual fNIRS as a reliable functional biomarker in clinical settings. To enhance clinical relevance, the development of standardized protocols, engaging stimuli, and age-stratified analyses is also crucial for improving diagnostic accuracy, tracking neurodevelopmental trajectories, and evaluating therapeutic interventions.